Pengujian Awal Pengaruh Faktor Internal dan Eksternal Perusahaan Terhadap Prediksi Kebangkrutan Perusahaan - Prawestri, Adhelia Desi; Azis, Abdul; Wiratno, Adi (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2016)
The purpose of this study is to determine the effect of internal factor with the earning management as a proxy, and eksternal factor with allowance for impairment of receivables as a proxy to the earning management. This study was a qualitative research with agricultural sector company as objects along 2012 to 2015. By using purposive sampling techiques intended that the data obtained more varied because it comes from varied sources. According to the results, it can be concluded that the internal factors of earning management with the other comprehensive income as a proxy had a positive influence on the prediction of bakruptcies in the agricultural sector and the external factors with external risk that described by premises allowance for impairment of receivables does not have an influence on the prediction of banrkruptcies in the agricultural sector in BEI.